Suitability of Motivation Expectancy–Value Model to Interpret Relations of Attitude, Self-Efficacy, and Effort with Achievement in Statistics and Expectation - Abdelfattah, Faisal (Jordan Journal of Educational Sciences, 2017)
Some psychological factors have been known to influence students’ achievement. Such factors may include: Attitudes toward statistics, self efficacy, and effort exerted in learning. The relationships between those factors and achievement were tested using structural equation modeling. Data were collected from 288 undergraduate students registered in Educational Statistics course. Three self-reported instruments have been used to measure students’ attitudes toward statistics, self efficacy and effort. Confirmatory factor analysis (CFA) confirmed the structure of self efficacy and effort instrument based on several fit indices. The findings from Structural Equation Modeling (SEM) showed a significant relationship between self efficacy and effort with achievement and expected grade in the course, but no significant relationship between attitudes toward statistics and both student achievement in the course and expected grade. This indicates that the expectancy-value model is appropriate as one of the motivational models, which can explain the variation of achievement in educational statistics through the appropriate fit indices that have emerged for the model